Formation of the System of Volunteer Activities of Students in Professional Development of a Pedagogue - Inna Yashchuk (Pedagogical Discourse, 2012)
The article deals with volunteering activity of students of the faculty of primary education and philology of Khmel’nyts’kyi Humanitarian-Pedagogical Academy in the context of formation of professional establishment of the future teacher.